Detecting meaningful body composition changes in athletes using dual-energy x-ray absorptiometry. (30th March 2016) - Colyer, Steffi L; Roberts, Simon P; Robinson, Jonathan B; Thompson, Dylan; Stokes, Keith A; Bilzon, James L J; Salo, Aki I T
Abstract: Dual-energy x-ray absorptiometry (DXA) imaging is considered to provide a valid and reliable estimation of body composition when stringent scanning protocols are adopted. However, applied practitioners are not always able to achieve this level of control and the subsequent impact on measurement precision is not always taken into account when evaluating longitudinal body composition changes. The primary aim of this study was to establish the reliability of DXA in an applied elite sport setting to investigate whether real body composition changes can be detected. Additionally, the performance implications of these changes during the training year were investigated. Forty-eight well-trained athletes (from four diverse sports) underwent two DXA scans using a 'real-world' approach (with limited pre-scan controls), typically within 48 h, to quantify typical error of measurement (TEM). Twenty-five athletes underwent further scans, before and after specific training and competition blocks. 'True' body composition changes were evaluated using 2 × TEM thresholds. Twelve bob skeleton athletes also performed countermovement jump and leg press tests at each time point. Many 'true' body composition changes were detected and coincided with the primary training emphases (e.g. lean mass gains during hypertrophy-based training). Clear relationships ( r ± 90% CI) were observed between performance changes (countermovement jump and leg press) and changes in lean mass (0.53 ± 0.26 and 0.35 ± 0.28, respectively) and fat mass (−0.44 ± 0.27 and −0.37 ± 0.28, respectively). DXA was able to detect real body composition changes without the use of stringent scanning controls. Associations between changes in body composition and performance demonstrated the potential influence of these changes on strength and power indices.